2002
DOI: 10.1093/ndt/17.9.1578
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endothelin antagonists on renal ischaemia-reperfusion injury and the development of acute renal failure in the rat

Abstract: The data show that both the ET(A)/ET(B) and selective ET(A)-receptor antagonist ameliorated the ischaemia-reperfusion injury when given in the peri-ischaemic period but not when the ET(A)-receptor antagonist was given for 60 min at 100 micro g/kg/min after the ischaemic period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Of all the vasoconstrictive agents, ET-1 seems to be particularly important, because its level increased after ischemia and blockage of the ET pathway by endothelin A receptor antagonists protects against renal IRI (12). In the present study, the expression of ET-1 in kidney was increased following IRI but was suppressed by IMD overexpression, likewise, through the antioxidative ability of IMD.…”
Section: Discussionsupporting
confidence: 51%
“…Of all the vasoconstrictive agents, ET-1 seems to be particularly important, because its level increased after ischemia and blockage of the ET pathway by endothelin A receptor antagonists protects against renal IRI (12). In the present study, the expression of ET-1 in kidney was increased following IRI but was suppressed by IMD overexpression, likewise, through the antioxidative ability of IMD.…”
Section: Discussionsupporting
confidence: 51%
“…This is consistent with the results of a previous study showing increased interleukin-8 levels and elevated numbers of neutrophilic granulocytes in the urine of DGF patients (Yarlagadda et al, 2008). The different perfusion intensities in different regions of the renal cortex suggest uneven distribution of resistance to renal microcirculation in DGF patients, which may be related to the pathological changes of terminal vasculature induced by ischemic reperfusion in the transplanted kidney (Inman et al, 2003;Huang et al, 2002). This may also be the mechanism of difference in the study by Angelescu et al (2003) (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…Using a thermal dissipation probe inserted into the cortex of the transplanted kidney, Angelescu et al (2003) found lower microcirculatory perfusion in DGF patients than in patients with a normally functioning transplanted kidney. In addition, ischemic reperfusion has been shown to result in increased serum levels of endothelin and endothelin-1, but decreased levels of the vasodilator nitric oxide, which increases vascular resistance in the transplanted kidney (Schilling et al, 1996;Huang et al, 2002;Inman et al, 2003;Perico et al, 2004;Zlotnick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The major drawback of most reports, however, is the fact, that ERAs were administrated prior to and during the ischaemic period. Later application during the reflow period was ineffective in most cases [73–77]. Importantly, the dual ET receptor antagonist tezosentan has recently been shown to prevent the rise in serum creatinine as well as tubular necrosis, and to improve inulin clearance even when administrated after ischaemia [71], suggesting that dual ERA may be potentially useful in the clinical setting.…”
Section: Role Of Endothelin In the Pathophysiology Of Acute Renal Faimentioning
confidence: 99%